Wybrane psychospołeczne predyktory procesu adaptacji do wdowieństwa starzejących się kobiet. Styl "odwiązania" od partnera = Selected psychosocial predictors of the process of adaptation to widowhood by aging women. The style of "detachment" from a partner - Niewiedział, Dorota (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents selected psychosocial factors modifying the process of adaptation to widowhood that occur in aging widows. In the present study, it was hypothesised that there is a style of "detachment" from a deceased life partner which is understood as the combination of a retrospective assessment of style of attachment to a partner and the sense of emotional andor social loneliness. The research performed on 124 widows (average duration of widowhood was 7.3 years) showed that there is a specific style of detachment from a partner in women with retrospective anxiety style of attachment in the past. A positive relation between a retrospective safe style of attachment and social loneliness requires further research.
Keywords: wdowieństwo; starzenie się kobiety; styl przywiązania do partnera; styl oderwania od partnera; widowhood; aging woman; attachment style from a partner; style of detachment from a partner